Optimum Wavelet Selection for Orthogonal Wavelet Division Multiplex (OWDM) Based Broadcasting System - Tarique, Mohammed (Discoveries in Agriculture and Food Sciences, 2016)
In the recent years Orthogonal Wavelet Division Multiplexing (OWDM) has been considered as an alternative of Orthogonal Frequency Division Multiplexing (OFDM). OWDM has lower computational complexity and higher flexibility compared to its OFDM counterpart. Wavelet is the most important element of an OWDM based system. Wavelets have been a much investigated topic in digital image processing for a long time. Recently they are being used in efficient communication system design. In this work we use wavelets in Digital Video Broadcasting-Terrestrial (DVB-T) system. Originally DVB-T system was designed based on OFDM. In this paper we use OWDM instead. We apply a number of wavelets namely Haar, Daubechies, Biorthogonal, Coiflets, and Symlets in OWDM design. The simulation results show that the Haar function outperforms other wavelets and hence this